Carbon-ceramic synergistic skeleton modified C / C composite material and preparation method thereof

By introducing ZrC ceramic powder using suction filtration technology during the ceramic modification process, a micro-nanocarbon-ceramic 3D synergistic reaction interface was constructed, and vacuum impregnation-drying and heat treatment were carried out, the problem of poor compatibility between the carbon matrix and the ceramic particle interface was solved, and the material performance was improved.

CN119638477AActive Publication Date: 2025-03-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411941252.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

During the existing ceramic modification process, the poor compatibility of the carbon matrix and the ceramic particles leads to a decline in material performance and limits its application.

Method used

The porous carbon matrix was obtained by curing, carbonizing and CVI treatment of impregnated resin. Then, ZrC ceramic powder was introduced using suction filtration technology to construct a micro-nanocarbon-ceramic 3D synergistic reaction interface, and carbon-ceramic synergistic framework modified C/C composite material was prepared by vacuum impregnation-drying and heat treatment.

Benefits of technology

It achieves uniform dispersion between carbon and ceramic interface and excellent interface compatibility, improving the ceramic conversion rate, overall density and comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638477A_ABST
    Figure CN119638477A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-ceramic synergistic skeleton modified C / C composite material and a preparation method thereof, and belongs to the technical field of ceramic modified C / C composite materials. The method disclosed by the invention comprises the following steps: immersing a low-density C / C composite material into an initial emulsion, and then sequentially carrying out heating curing, drying, carbonization and deposition pyrolytic carbon treatment to obtain a porous carbon matrix; introducing the ZrC turbid liquid into a porous carbon matrix through suction filtration treatment to obtain a carbon matrix containing a carbon-ceramic synergistic skeleton; the preparation method comprises the following steps: dipping a carbon matrix containing a carbon-ceramic synergistic skeleton in an organic zirconium polymer solution, and carrying out vacuum dipping-drying and heat treatment for several times to obtain a carbon-ceramic synergistic skeleton modified C / C composite material; according to the method, the interface reaction of carbon and ceramic can be adjusted by adjusting suction filtration parameters, and the technical problem that in the ceramic modification process, the interface compatibility of a carbon matrix and ceramic particles is poor is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic modified C / C composite materials, and specifically relates to a carbon-ceramic synergistic skeleton modified C / C composite material and a preparation method thereof. Background Art

[0002] Carbon / carbon (C / C) composites have excellent properties such as high specific strength / specific modulus, high high-temperature strength retention, and low thermal expansion coefficient. They are ideal ultra-high temperature structural materials and play an important role in the development of new aerospace vehicles. However, C / C composites will suffer oxidation damage in an aerobic environment above 450°C, resulting in a significant decrease in the performance of C / C composites, which seriously restricts their application in high-temperature oxygen-containing environments. Studies have shown that the introduction of ultra-high temperature ceramics (UHTCs) such as carbides and borides is an effective way to improve the oxidation and ablation resistance of C / C composites. Common ultra-high temperature ceramic matrix modification methods include chemical vapor infiltration (CVI), slurry infiltration (SI), reactive melt infiltration (RMI), precursor impregnation-pyrolysis (PIP), and their combined processes. Compared with other C / C-UHTCs composite preparation processes, PIP has a low preparation temperature and good material structure designability. It can achieve near-net-size molding of large and complex-shaped components and obtain a high-purity ceramic matrix.

[0003] Studies have shown that regulating and modifying the pore structure of the preform is conducive to achieving a controllable and uniform distribution of the ceramic phase in the composite material, which is of great significance for improving the performance of the material. However, ZrC ceramics can theoretically completely fill the porous C / C composite material, but in the precursor impregnation-cracking process, the ceramic conversion rate of the precursor solution is only 40-50%; at the same time, gas escape and volume shrinkage will inevitably occur during the high-temperature pyrolysis ceramicization process, and there are many micropores inside the obtained ceramic matrix. After the ceramic is introduced into the carbon matrix, a large number of interfaces are formed between the ceramic phase and the porous carbon matrix. Due to the intrinsic brittleness of the ceramic and the inevitable interfacial reaction with the carbon matrix, residual thermal stress exceeding the strength of the matrix will be introduced into the matrix, and its mechanical properties will usually be reduced, which will lead to a decrease in the comprehensive performance of the composite material, greatly limiting the application of the composite material. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon-ceramic synergistic skeleton modified C / C composite material and a preparation method thereof, so as to solve the technical problem of poor interface compatibility between carbon matrix and ceramic particles in the existing ceramic modification process.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material, comprising the following steps: The low-density C / C composite material is immersed in the initial emulsion, and then subjected to heating curing, drying, carbonization and pyrolytic carbon deposition treatments in sequence to obtain a porous carbon matrix; The ZrC suspension is introduced into the porous carbon matrix by suction filtration to obtain a carbon matrix containing a carbon-ceramic synergistic framework; The carbon matrix containing the carbon-ceramic synergistic framework is impregnated in an organic zirconium polymer solution, and vacuum impregnation-drying and heat treatment are performed several times to obtain a carbon-ceramic synergistic framework modified C / C composite material.

[0006] Furthermore, the curing treatment is carried out in an oven; the curing treatment temperature is 70-90°C and the time is 24-36 hours; the drying is carried out at normal pressure, 80-120°C, and the drying is carried out for 5-10 hours.

[0007] Furthermore, the carbonization parameters are: in an argon atmosphere, heating to 750-1000°C at 2-10°C / min, and keeping the temperature for 2-4 h; The parameters of the deposition pyrolytic carbon treatment are as follows: using argon as the protective gas, heating the heating device to 900-1100 °C at a heating rate of 1-5 °C / min, and then introducing CH 4 The deposition time was 40-300 min, and the porous carbon matrix was obtained after cooling to room temperature. During the heating and cooling process, the flow rate of argon gas was 1-3 L / min. CH 4 During deposition, the flow rate of argon gas is 2~5L / min.

[0008] Furthermore, the ZrC suspension is obtained by mixing ZrC powder and anhydrous ethanol; the particle size of the ZrC powder is 100nm~2μm; and the mass ratio of the ZrC powder to anhydrous ethanol is (5~15)g:(15~35)g.

[0009] Furthermore, the step of introducing the ZrC suspension into the porous carbon matrix by suction filtration is: The ZrC suspension is introduced into the porous carbon matrix using a suction filtration device. After the ZrC suspension on the surface of the porous carbon matrix is ​​drained, the ZrC suspension is continued to be added dropwise for several cycles until the ZrC suspension on the surface of the porous carbon matrix can no longer be absorbed. After drying, a carbon matrix containing a carbon-ceramic synergistic skeleton is obtained.

[0010] Furthermore, in the process of obtaining the carbon matrix containing the carbon-ceramic synergistic framework, the drying temperature is 70-100° C. and the drying time is 8-10 h; The number of cycles is 3 to 5 times.

[0011] Furthermore, the organic zirconium polymer solution is obtained by stirring and mixing an organic zirconium polymer and xylene; The stirring method is magnetic stirring; the magnetic stirring time is 1 to 4 hours; The usage ratio of the organic zirconium polymer and xylene is (60-70) g: (30-40) g.

[0012] Furthermore, the number of cycles of the vacuum impregnation-drying and heat treatment is 2 to 9 times.

[0013] Furthermore, the heat treatment parameters are: in an argon atmosphere, heating to 1500-1600°C at a heating rate of 5-10°C / min, and heating for 2-3 h.

[0014] The invention also discloses a carbon-ceramic synergistic skeleton modified C / C composite material prepared by the preparation method.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a carbon-ceramic synergistic skeleton modified C / C composite material. A porous carbon matrix with a suitable pore structure and high stability is obtained by impregnating resin, curing, carbonizing and CVI. Subsequently, ZrC ceramic powder is introduced by filtration technology to construct a micro-nano carbon-ceramic 3D synergistic reaction interface. The treated composite material has uniform dispersibility and excellent interface compatibility. Finally, vacuum impregnation-drying and heat treatment are used to prepare the carbon-ceramic synergistic skeleton modified C / C composite material. The method can adjust the interface reaction between carbon and ceramic by adjusting the filtration parameters, thereby solving the technical problem of poor interface compatibility between the carbon matrix and ceramic particles during the ceramic modification process.

[0016] Furthermore, by introducing ZrC ceramic powder into the porous carbon matrix, the content of the introduced ZrC ceramic powder can be controlled according to the changes in the particle size of the ZrC ceramic powder and the number of filtration times, thereby constructing a 3D reaction interface, which can help reduce the nucleation work, increase the driving force required for nucleation, promote crystal nucleation, and facilitate the subsequent formation of new ceramic phases, thereby effectively improving the ceramic conversion rate, thereby improving the internal ceramic density of the material prepared by the traditional matrix modification technology.

[0017] Furthermore, after the introduction of ZrC ceramic powder, its particle size and surface morphology significantly affect the interfacial adsorption; smaller particle size increases the interfacial specific surface area and improves its surface energy, making it easier to interact; in addition, rough and porous nano-ceramic particles have a higher specific surface area and more active sites, making it easier to adsorb; the physical adsorption at the interface is combined with chemical bonding, and the adsorption capacity is greatly improved, which can significantly enhance the tightness of the ZrC ceramic introduced during the vacuum impregnation-drying and heat treatment process of the organic zirconium polymer solution and the carbon matrix, thereby improving the overall density and comprehensive performance of the composite material.

[0018] The present invention also discloses a carbon-ceramic synergistic skeleton modified C / C composite material prepared by the above method. By introducing ceramic powder with a particle size suitable for the pores of the porous matrix, a "carbon-ceramic" micro-nano synergistic 3D structure is constructed, so that it has a highly compatible reaction interface, the ceramic conversion rate is improved, the carbon matrix and the ceramic matrix are more strongly bonded, the stress transfer efficiency between the fiber and the matrix is ​​improved, and the stress concentration inside the material is alleviated; in addition, the composite material with a "carbon-ceramic" micro-nano synergistic structural interface will have better anti-oxidation and ablation performance. Therefore, the strengthening effect on the interface is the key to optimizing the overall performance of the ceramic modified C / C composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The figure is a flow chart of the preparation of the carbon-ceramic synergistic skeleton modified C / C composite material of the present invention; Figure 2 is a morphology diagram of the porous carbon substrate prepared in Example 1; Among them: a-50μm; b-10μm; Figure 3 is a SEM image of the carbon matrix containing the carbon-ceramic synergistic framework prepared in Example 1; Figure 4 The X-ray diffraction pattern of the carbon-ceramic synergistic skeleton modified C / C composite material prepared in Example 1; Figure 5 Comparison of SEM images of cross sections of different composite materials; Among them: a-carbon-ceramic synergistic skeleton modified C / C composite material; b-conventional ZrC ceramic modified C / C composite material. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0025] like Figure 1 As shown, the present invention provides a method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material, comprising the following steps: The low-density C / C composite material is immersed in the initial emulsion, and then subjected to heating curing, drying, carbonization and pyrolytic carbon deposition treatments in sequence to obtain a porous carbon matrix; The ZrC suspension is introduced into the porous carbon matrix by suction filtration to obtain a carbon matrix containing a carbon-ceramic synergistic framework; The carbon matrix containing the carbon-ceramic synergistic framework is impregnated in an organic zirconium polymer solution, and vacuum impregnation-drying and heat treatment are performed several times to obtain a carbon-ceramic synergistic framework modified C / C composite material.

[0026] Preferably, the preparation method of the initial emulsion is: Resorcinol and formaldehyde solution are dissolved in anhydrous ethanol, hexadecyltrimethylammonium bromide is added, and the mixture is stirred to obtain an initial emulsion.

[0027] Furthermore, the dosage ratio of the resorcinol, the formaldehyde solution, the anhydrous ethanol and the hexadecyltrimethylammonium bromide is (12.0-15.0) g: (12.6-18) g: (16.6-20.6) mL: (0.024-0.24) g; The stirring method is magnetic stirring; the time of the magnetic stirring is 10 to 20 minutes; The mass concentration of the formaldehyde solution is 37.5wt.%.

[0028] Preferably, the heating and curing process is: placing the C / C composite material impregnated with the initial emulsion in an oven at 70-90° C. for heating and curing for 24-36 hours.

[0029] Preferably, the drying is carried out at normal pressure, 100-120° C., for 8-10 h.

[0030] Preferably, the carbonization process parameters are: in an argon atmosphere, heating to 750-1000°C at 2-10°C / min and keeping the temperature for 2-4 h.

[0031] Preferably, the specific process of depositing pyrolytic carbon treatment is: The C / C composite material containing a porous skeleton was placed in a vertical CVD furnace. Argon was used as the protective gas. The heating equipment was heated to 900-1100 °C at a heating rate of 3-5 °C / min. Then CH 4 Pyrolytic carbon (PyC) was deposited for 40-300 min and the porous carbon matrix was obtained after cooling to room temperature; During the heating and cooling processes, the flow rate of argon gas was 1~3 L / min; during the deposition of PyC, the flow rate of argon gas was 2~5 L / min.

[0032] Preferably, the specific process of the suction filtration treatment is: adding the ZrC powder to anhydrous ethanol, stirring to form a uniform suspension, introducing the uniform ZrC suspension into the porous carbon matrix by using a suction filtration device, and continuing to drip the suspension after the suspension on the surface of the porous carbon matrix is ​​drained, and the cycle is repeated several times until the suspension on the surface can no longer be absorbed, and a carbon matrix containing a carbon-ceramic synergistic skeleton is obtained after drying; Among them, the particle size of ZrC powder is 100nm~2μm, the mass is 5~15g; the mass of anhydrous ethanol is 15~35g; the drying method is 70~100℃, 8~10h; The number of cycles is 3 to 5 times; the drying temperature is 70 to 100°C.

[0033] Preferably, the organic zirconium polymer solution is obtained by mixing an organic zirconium polymer and xylene and subjecting the mixture to magnetic stirring for 2 to 4 hours; the amount ratio of the organic zirconium polymer to xylene is (60 to 70) g: (30 to 40) g; The number of vacuum impregnation-drying is 2 to 3 times; The process parameters of the heat treatment are: in an argon atmosphere, heating to 1500-1600°C at a heating rate of 5-10°C / min for 2-3 hours; The number of vacuum impregnation-drying-heat treatment cycles is 7 to 9 times.

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0035] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0036] Example 1 A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material comprises the following steps: Step 1: 12.0 g of resorcinol and 12.6 g of 37.5 wt.% formaldehyde solution were dissolved in 16.6 mL of anhydrous ethanol to obtain a mixture; 0.024 g of hexadecyltrimethylammonium bromide (CTAB) was added to the mixture, and the suspension was magnetically stirred for 10 minutes to obtain a transparent initial emulsion.

[0037] Step 2: Immerse the low-density C / C in the initial emulsion obtained in step 1 so that the block is completely immersed, then place it in a vacuum drying oven, evacuate the box until the pressure inside the box is less than 0.09 MPa, and maintain it for 30 minutes. Then, after heating and curing, drying at normal pressure and carbonization, place it in a CVI furnace, use argon as the protective gas, and heat the equipment to 900 °C at a heating rate of 3 °C / min, and then introduce CH 4 PyC was deposited for 40 min.

[0038] The heating curing, atmospheric pressure drying and carbonization process is as follows: the low-density C / C composite material is cured in an oven at 70°C for 24 hours, and then dried at 80°C for 5 hours; then placed in a tubular furnace, heated to 750°C at 2°C / min, and kept warm for 2 hours, with argon gas introduced as a protective gas throughout the process to crack the resin gel in the composite material into carbon; The pyrolytic carbon deposition process is as follows: the argon flow rate is set to 1 L / min during the temperature rise and fall process, and 2 L / min during the deposition process. 4 The flow rate was 70 L / min; then the temperature was lowered to room temperature to obtain a porous carbon matrix.

[0039] Step 3, preparation of carbon-ceramic synergistic skeleton matrix: Take 5g of ZrC powder with a particle size of 100nm and add it to 15g of anhydrous ethanol. Stir to form a uniform suspension. Use a suction filtration device to introduce the uniform ZrC suspension into the porous carbon matrix. After the suspension on the surface of the porous carbon matrix is ​​drained, continue to add the suspension. Repeat this cycle for 3 times until the suspension on the surface can no longer be absorbed. Place it in a 70℃ oven and dry it for 8h to obtain a matrix containing a carbon-ceramic synergistic skeleton.

[0040] Step 4, Precursor Impregnation-Pyrolysis (PIP): 60 g of organic zirconium polymer (PZC) was added to 30 g of xylene, and magnetic stirring was performed for 1.5 h to obtain a uniform PZC solution (precursor solution). Subsequently, the matrix of the carbon-ceramic synergistic skeleton obtained in step 3 was immersed in the precursor solution so that the block was completely immersed, and vacuum impregnation-drying was repeated twice. The dried composite material was placed in a high-temperature furnace for heat treatment. After 7 repeated impregnation-cracking and heat treatment, a carbon-ceramic synergistic skeleton modified C / C composite material was obtained. Among them, the heat treatment process for preparing C / C-ZrC composite materials using the PIP method is: placing the dried composite material in a high-temperature furnace, introducing argon as a protective gas, heating the equipment to 1600 °C at a heating rate of 5 °C / min for 2 h, so that the introduced precursor is cracked and converted into ZrC ceramics.

[0041] Example 2 A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material comprises the following steps: Step 1: 13.0 g of resorcinol and 15.6 g of 37.5 wt.% formaldehyde solution were dissolved in 18.6 mL of anhydrous ethanol to obtain a mixture; 0.036 g of hexadecyltrimethylammonium bromide (CTAB) was added to the mixture, and the suspension was magnetically stirred for 15 minutes to obtain a transparent initial emulsion.

[0042] Step 2: Immerse the low-density C / C in the initial emulsion obtained in step 1 so that the block is completely immersed, then place it in a vacuum drying oven, evacuate the box until the pressure inside the box is less than 0.09 MPa, and maintain it for 40 minutes. Then, after heating and curing, drying at normal pressure and carbonization, place it in a CVI furnace, use argon as the protective gas, and heat the equipment to 950 °C at a heating rate of 3 °C / min, and then introduce CH 4 PyC was deposited for 80 min.

[0043] The curing, drying and carbonization process is as follows: the low-density C / C composite material is cured in an oven at 80°C for 24 h, and then dried at 90°C under normal pressure for 5 h; then it is placed in a tubular furnace, heated to 1000°C at 3°C / min, and kept warm for 2 h, with argon gas introduced as a protective gas throughout the process to crack the resin gel in the composite material into carbon; The pyrolytic carbon deposition process is as follows: the argon flow rate is set to 3 L / min during the temperature rise and fall process, and 5 L / min during the deposition process. 4 The flow rate was 90 L / min; pyrolytic carbon was deposited for 300 min; and then the temperature was cooled to room temperature to obtain a porous carbon matrix.

[0044] Step 3, preparation of carbon-ceramic synergistic skeleton matrix: Take 10g of ZrC powder with a particle size of 200nm and add it to 25g of anhydrous ethanol. Stir to form a uniform suspension. Use a suction filtration device to introduce the uniform ZrC suspension into the porous carbon matrix. After the suspension on the surface of the porous carbon matrix is ​​drained, continue to add the suspension. Repeat 5 times until the suspension on the upper surface can no longer be absorbed. Place it in a 70℃ oven and dry it for 9h to obtain a matrix containing a carbon-ceramic synergistic skeleton.

[0045] Step 4, Precursor Impregnation-Pyrolysis (PIP): 66 g of organic zirconium polymer (PZC) was added to 33 g of xylene, and magnetic stirring was performed for 2 h to obtain a uniform PZC solution (precursor solution). Subsequently, the matrix of the carbon-ceramic synergistic skeleton obtained in step 3 was immersed in the precursor solution so that the block was completely immersed, and vacuum impregnation-drying was repeated twice. The dried composite material was placed in a high-temperature furnace for heat treatment. After 8 repeated impregnation-cracking and heat treatment, a carbon-ceramic synergistic skeleton modified C / C composite material was obtained; Among them, the heat treatment process for preparing C / C-ZrC composite materials using the PIP method is: placing the dried composite material in a high-temperature furnace, introducing argon as a protective gas, heating the equipment to 1550 °C at a heating rate of 5 °C / min for 2 h, so that the introduced precursor is cracked and converted into ZrC ceramics.

[0046] Example 3 A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material comprises the following steps: Step 1: 14.0 g of resorcinol and 16.6 g of 37.5 wt.% formaldehyde solution were dissolved in 20.6 mL of anhydrous ethanol to obtain a mixture; 0.16 g of hexadecyltrimethylammonium bromide (CTAB) was added to the mixture, and the suspension was magnetically stirred for 20 minutes to obtain a transparent initial emulsion.

[0047] Step 2: Immerse the low-density C / C in the initial emulsion obtained in step 1 so that the block is completely immersed, then place it in a vacuum drying oven, evacuate the box until the pressure inside the box is less than 0.09 MPa, and maintain it for 35 minutes. Then, after heating and curing, drying at normal pressure and carbonization, place it in a CVI furnace, use argon as the protective gas, and heat the equipment to 1000 °C at a heating rate of 4 °C / min, and then introduce CH 4 PyC was deposited for 60 min.

[0048] The curing, drying and carbonization process is as follows: the low-density C / C composite material is cured in an oven at 70°C for 24 hours, and then dried at 80°C under normal pressure for 5 hours; then it is placed in a tubular furnace, heated to 900°C at 2°C / min, and kept warm for 2 hours, with argon gas introduced as a protective gas throughout the process to crack the resin gel in the composite material into carbon; The pyrolytic carbon deposition process is as follows: the argon flow rate is set to 2 L / min during the heating and cooling process, 4 L / min during the deposition process, and CH 4 The flow rate was 80 L / min; then the temperature was lowered to room temperature to obtain a porous carbon matrix.

[0049] Step 3, preparation of carbon-ceramic synergistic skeleton matrix: Take 10g of ZrC powder with a particle size of 1.5μm and add it to 30g of anhydrous ethanol. Stir to form a uniform suspension. Use a suction filtration device to introduce the uniform ZrC suspension into the porous carbon matrix. After the suspension on the surface of the porous carbon matrix is ​​drained, continue to add the suspension. Repeat 4 times until the suspension on the surface can no longer be absorbed. Place it in a 70℃ oven and dry it for 9h to obtain a matrix containing a carbon-ceramic synergistic skeleton.

[0050] Step 4, Precursor Impregnation-Pyrolysis (PIP): 70 g of organic zirconium polymer (PZC) was added to 40 g of xylene, and magnetic stirring was performed for 2 h to obtain a uniform PZC solution (precursor solution). Subsequently, the matrix of the carbon-ceramic synergistic skeleton obtained in step 3 was immersed in the precursor solution so that the block was completely immersed, and vacuum impregnation-drying was repeated 3 times. The dried composite material was placed in a high-temperature furnace for heat treatment. After 8 repeated impregnation-cracking and heat treatment, a carbon-ceramic synergistic skeleton modified C / C composite material was obtained. Among them, the heat treatment process for preparing C / C-ZrC composite materials using the PIP method is: placing the dried composite material in a high-temperature furnace, introducing argon as a protective gas, heating the equipment to 1500 ℃ at a heating rate of 5 ℃ / min for 2 h, so that the introduced precursor is cracked and converted into ZrC ceramics.

[0051] Example 4 A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material comprises the following steps: Step 1: 15.0 g of resorcinol and 14.6 g of 37.5 wt.% formaldehyde solution were dissolved in 20.6 mL of anhydrous ethanol to obtain a mixture; 0.08 g of hexadecyltrimethylammonium bromide (CTAB) was added to the mixture, and the suspension was magnetically stirred for 20 minutes to obtain a transparent initial emulsion.

[0052] Step 2: Immerse the low-density C / C in the initial emulsion obtained in step 1 so that the block is completely immersed, then place it in a vacuum drying oven, evacuate the box until the pressure inside the box is less than 0.09 MPa, and maintain it for 30 minutes. Then, heat it in a water bath for curing, dry it at normal pressure, and carbonize it. Then, place it in a CVI furnace, use argon as the protective gas, and heat the equipment to 900 °C at a heating rate of 3 °C / min, and then introduce CH 4 PyC was deposited for 100 min.

[0053] The curing, drying and carbonization process is as follows: the low-density C / C composite material is cured in an oven at 70°C for 24 hours, and then dried at 80°C under normal pressure for 5 hours; then it is placed in a tubular furnace and heated to 900°C at 2°C / min and kept at this temperature for 2 hours, with argon gas introduced as a protective gas throughout the process to crack the resin gel in the composite material into carbon; The pyrolytic carbon deposition process is as follows: the argon flow rate is set to 1 L / min during the temperature rise and fall process, and 2 L / min during the deposition process. 4 The flow rate was 70 L / min; then the temperature was lowered to room temperature to obtain a porous carbon matrix.

[0054] Step 3, preparation of carbon-ceramic synergistic skeleton matrix: Take 12g of ZrC powder with a particle size of 2μm and add it to 18g of anhydrous ethanol. Stir to form a uniform suspension. Use a suction filtration device to introduce the uniform ZrC suspension into the porous carbon matrix. After the suspension on the surface of the porous carbon matrix is ​​drained, continue to add the suspension. Repeat 5 times until the suspension on the upper surface can no longer be absorbed. Place it in a 70°C oven and dry it for 8h to obtain a matrix containing a carbon-ceramic synergistic skeleton.

[0055] Step 4, Precursor Impregnation-Pyrolysis (PIP): 65 g of organic zirconium polymer (PZC) was added to 35 g of xylene, and magnetic stirring was performed for 1.5 h to obtain a uniform PZC solution (precursor solution). Subsequently, the matrix of the carbon-ceramic synergistic skeleton obtained in step 3 was immersed in the precursor solution so that the block was completely immersed, and vacuum impregnation-drying was repeated 3 times. The dried composite material was placed in a high-temperature furnace for heat treatment. After 7 repeated impregnation-cracking and heat treatment, a carbon-ceramic synergistic skeleton modified C / C composite material was obtained. Among them, the heat treatment process for preparing C / C-ZrC composite materials using the PIP method is: placing the dried composite material in a high-temperature furnace, introducing argon as a protective gas, heating the equipment to 1600 °C at a heating rate of 5 °C / min for 2 h, so that the introduced precursor is cracked and converted into ZrC ceramics.

[0056] Example 5 A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material comprises the following steps: Step 1: 12.0 g of resorcinol and 16 g of 37.5 wt.% formaldehyde solution were dissolved in 19.6 mL of anhydrous ethanol to obtain a mixture; 0.24 g of hexadecyltrimethylammonium bromide (CTAB) was added to the mixture, and the suspension was magnetically stirred for 20 min to obtain a transparent initial emulsion.

[0057] Step 2: Immerse the low-density C / C in the initial emulsion obtained in step 1 so that the block is completely immersed, then place it in a vacuum drying oven, evacuate the box until the pressure inside is less than 0.09 MPa, and maintain it for 30 min. Then, heat it in a water bath for curing, dry it at normal pressure, and carbonize it. Then, place it in a CVI furnace, use argon as the protective gas, and heat the equipment to 1100 °C at a heating rate of 3 °C / min, then introduce CH 4 PyC was deposited for 250 min.

[0058] The curing, drying and carbonization process is as follows: the low-density C / C composite material is cured in an oven at 70 °C for 24 hours, and then dried at 80 °C under normal pressure for 5 hours; then placed in a tubular furnace, heated to 900 °C at 2 °C / min, and kept warm for 2 hours, with argon gas introduced as a protective gas throughout the process to crack the resin gel in the composite material into carbon; The pyrolytic carbon deposition process is as follows: the argon flow rate is set to 2 L / min during the heating and cooling process, 4 L / min during the deposition process, and CH 4 The flow rate was 70 L / min; then the temperature was lowered to room temperature to obtain a porous carbon matrix.

[0059] Step 3, preparation of carbon-ceramic synergistic skeleton matrix: Take 14 g of ZrC powder with a particle size of 1.5 μm and add it to 28 g of anhydrous ethanol. Stir to form a uniform suspension. Use a suction filtration device to introduce the uniform ZrC suspension into the porous carbon matrix. After the suspension on the surface of the porous carbon matrix is ​​drained, continue to add the suspension dropwise. Repeat 5 times until the suspension on the surface can no longer be absorbed. Place it in a 70 °C oven and dry it for 8 h to obtain a matrix containing a carbon-ceramic synergistic skeleton.

[0060] Step 4, Precursor Impregnation-Pyrolysis (PIP): 60 g of organic zirconium polymer (PZC) was added to 40 g of xylene, and magnetic stirring was performed for 1.5 h to obtain a uniform PZC solution (precursor solution). Subsequently, the matrix of the carbon-ceramic synergistic skeleton obtained in step 3 was immersed in the precursor solution so that the block was completely immersed, and vacuum impregnation-drying was repeated 3 times. The dried composite material was placed in a high-temperature furnace for heat treatment. After 9 repeated impregnation-cracking and heat treatment, a carbon-ceramic synergistic skeleton modified C / C composite material was obtained. Among them, the heat treatment process for preparing C / C-ZrC composite materials using the PIP method is as follows: the dried composite material is placed in a high-temperature furnace, argon is introduced as a protective gas, the equipment is heated to 1550 ℃ at a heating rate of 5 ℃ / min for heat treatment for 2 h, so that the introduced precursor is cracked and converted into ZrC ceramics.

[0061] Example 5 A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material comprises the following steps: Step 1: 12.0 g of resorcinol and 16 g of 37.5 wt.% formaldehyde solution were dissolved in 19.6 mL of anhydrous ethanol to obtain a mixture; 0.24 g of hexadecyltrimethylammonium bromide (CTAB) was added to the mixture, and the suspension was magnetically stirred for 20 min to obtain a transparent initial emulsion.

[0062] Step 2: Immerse the low-density C / C in the initial emulsion obtained in step 1 so that the block is completely immersed, then place it in a vacuum drying oven, evacuate the box until the pressure inside is less than 0.09 MPa, and maintain it for 30 min. Then, heat it in a water bath for curing, dry it at normal pressure, and carbonize it. Then, place it in a CVI furnace, use argon as the protective gas, and heat the equipment to 1100 °C at a heating rate of 5 °C / min, and then introduce CH 4 PyC was deposited for 300 min.

[0063] The curing, drying and carbonization process is as follows: the low-density C / C composite material is cured in an oven at 90 °C for 36 hours, and then dried at 120 °C under normal pressure for 10 hours; then it is placed in a tubular furnace, heated to 1100 °C at 5 °C / min, and kept warm for 2 hours, with argon gas introduced as a protective gas throughout the process to crack the resin gel in the composite material into carbon; The pyrolytic carbon deposition process is as follows: the argon flow rate is set to 2 L / min during the heating and cooling process, 4 L / min during the deposition process, and CH 4 The flow rate was 70 L / min; then the temperature was lowered to room temperature to obtain a porous carbon matrix.

[0064] Step 3, preparation of carbon-ceramic synergistic skeleton matrix: Take 15 g of ZrC powder with a particle size of 1.5 μm and add it to 35 g of anhydrous ethanol. Stir to form a uniform suspension. Use a suction filtration device to introduce the uniform ZrC suspension into the porous carbon matrix. After the suspension on the surface of the porous carbon matrix is ​​drained, continue to add the suspension dropwise. Repeat 5 times until the suspension on the surface can no longer be absorbed. Place it in a 100 °C oven and dry it for 10 h to obtain a matrix containing a carbon-ceramic synergistic skeleton.

[0065] Step 4, Precursor Impregnation-Pyrolysis (PIP): 60 g of organic zirconium polymer (PZC) was added to 40 g of xylene, and magnetic stirring was performed for 4 h to obtain a uniform PZC solution (precursor solution). Subsequently, the matrix of the carbon-ceramic synergistic skeleton obtained in step 3 was immersed in the precursor solution so that the block was completely immersed, and vacuum impregnation-drying was repeated 9 times. The dried composite material was placed in a high-temperature furnace for heat treatment. After 9 repeated impregnation-cracking and heat treatment, a carbon-ceramic synergistic skeleton modified C / C composite material was obtained; Among them, the heat treatment process for preparing C / C-ZrC composite materials using the PIP method is as follows: the dried composite material is placed in a high-temperature furnace, argon is introduced as a protective gas, the equipment is heated to 1550 ℃ at a heating rate of 10 ℃ / min for heat treatment for 3 h, so that the introduced precursor is cracked and converted into ZrC ceramics.

[0066] Figure 2 This is the morphology of the porous carbon matrix prepared in Example 1. It can be seen from the figure that the porous carbon has a three-dimensional connected pore structure and a continuously stacked carbon particle skeleton. The pore size and pore wall size can reach the micron level. The carbon particles are relatively uniform and have the function of dividing and refining the pores.

[0067] Figure 3 This is a SEM image of the carbon matrix containing a carbon-ceramic synergistic skeleton prepared in Example 1; as can be seen from the figure, after filtration treatment, the ZrC particles are successfully adsorbed on the porous carbon skeleton particles, thereby constructing a 3D reaction interface, which is beneficial to improving the interface compatibility.

[0068] Figure 4 This is the X-ray diffraction pattern of the carbon-ceramic synergistic skeleton modified C / C composite material prepared in Example 1; it can be seen from the figure that a pure ZrC modified C / C composite material was successfully prepared.

[0069] Figure 5 Comparison of SEM images of cross sections of different composite materials; Figure 5It can be seen that in the conventional ZrC ceramic modified C / C composite material, the ZrC ceramic structure is relatively loose, with micropores and cracks. Its structure is relatively loose and not dense enough. At the same time, the ceramic particles inside the sample CZ are agglomerated, the particle size is large, and it presents a continuous lamellar distribution; while in the C / C composite material modified by the carbon-ceramic synergistic skeleton, the construction of the 3D reaction interface makes the porous carbon skeleton and ZrC dispersed and evenly distributed, alleviating the uneven infiltration of the ceramic matrix and the low ceramic conversion rate. The ZrC ceramic particles are small, tightly combined, and are characterized by a mosaic distribution with the porous carbon skeleton.

[0070] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material, characterized in that: The following steps are involved: The low-density C / C composite material is immersed in the initial emulsion, and then subjected to heating curing, drying, carbonization and pyrolytic carbon deposition treatments in sequence to obtain a porous carbon matrix; The ZrC suspension is introduced into the porous carbon matrix by suction filtration to obtain a carbon matrix containing a carbon-ceramic synergistic framework; The carbon matrix containing the carbon-ceramic synergistic framework is impregnated in an organic zirconium polymer solution, and vacuum impregnation-drying and heat treatment are performed several times to obtain a carbon-ceramic synergistic framework modified C / C composite material.

2. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The curing treatment is carried out in an oven; the curing treatment temperature is 70-90°C and the time is 24-36 hours; the drying is carried out at normal pressure and 80-120°C for 5-10 hours.

3. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The carbonization parameters are: in an argon atmosphere, heating to 750-1000°C at 2-10°C / min, and keeping the temperature for 2-4 hours; The parameters of the deposition pyrolytic carbon treatment are as follows: using argon as a protective gas, heating the heating equipment to 900-1100°C at a heating rate of 1-5°C / min, then introducing CH4 for deposition for 40-300 min, and cooling to room temperature to obtain a porous carbon matrix; wherein, during the heating and cooling processes, the flow rate of argon is 1-3 L / min; when introducing CH4 for deposition, the flow rate of argon is 2-5 L / min.

4. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The ZrC suspension is obtained by mixing ZrC powder and anhydrous ethanol; the particle size of the ZrC powder is 100nm~2μm; the mass ratio of the ZrC powder to anhydrous ethanol is (5~15)g:(15~35)g.

5. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The step of introducing the ZrC suspension into the porous carbon matrix by suction filtration is as follows: The ZrC suspension is introduced into the porous carbon matrix using a suction filtration device. After the ZrC suspension on the surface of the porous carbon matrix is ​​drained, the ZrC suspension is continued to be added dropwise for several cycles until the ZrC suspension on the surface of the porous carbon matrix can no longer be absorbed. After drying, a carbon matrix containing a carbon-ceramic synergistic skeleton is obtained.

6. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 5, characterized in that: In the process of obtaining the carbon matrix containing the carbon-ceramic synergistic framework, the drying temperature is 70-100°C and the time is 8-10 hours; The number of cycles is 3 to 5 times.

7. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The organic zirconium polymer solution is obtained by stirring and mixing the organic zirconium polymer and xylene; The stirring method is magnetic stirring; the magnetic stirring time is 1 to 4 hours; The usage ratio of the organic zirconium polymer and xylene is (60-70) g: (30-40) g.

8. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The number of cycles of the vacuum impregnation-drying and heat treatment is 2 to 9 times.

9. The method for preparing a carbon-ceramic synergistic skeleton modified C / C composite material according to claim 1, characterized in that: The heat treatment parameters are: in an argon atmosphere, heating to 1500-1600°C at a heating rate of 5-10°C / min for 2-3 hours.

10. A carbon-ceramic synergistic skeleton modified C / C composite material, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparing method of SiC-ZrC gradient modified carbon / carbon composite material

    CN106045550A

  • Preparation method of in-situ synthesis silicon carbide nanowire network modified carbon / carbon composite material

    CN113860875A

  • ZrB2-ZrC-SiC modified carbon / carbon composite material as well as preparation method and application thereof

    CN116120080A

  • Preparation method of fiber toughened ceramic-based composite material

    CN117964380A

  • Porous carbon-assisted ZrC modified C / C composite material and preparation method thereof

    CN118420374A